2011
DOI: 10.2174/187569211796957575
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomic Research in South Africa: Lessons Learned and Future Opportunities in the Rainbow Nation

Abstract: South Africa, like many other developing countries, stands to benefit from novel diagnostics and drugs developed by pharmacogenomics guidance due to high prevalence of disease burden in the region. This includes both communicable (e.g., HIV/AIDS and tuberculosis) and non-communicable (e.g., diabetes and cardiovascular) diseases. For example, although only 0.7% of the world’s population lives in South Africa, the country carries 17% of the global HIV/AIDS burden and 5% of the global tuberculosis burden. Nobel P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 124 publications
1
60
0
Order By: Relevance
“…Significant disparities currently exist among SSA countries in genomics research capacity (Adedokun et al 2016). South Africa has the highest genomics research output, which is reflected in the investments made in its genomics and biotechnology sector (Hardy et al 2008;Warnich et al 2011;Ndimba and Thomas 2008;Motari et al 2004). The study findings call for African governments to increase their investments in building local capacity, provide a sustainable research environment, and encourage joint genomics research among those affiliated with SSA universities.…”
Section: Overcoming Obstacles/challenges To Facilitate Translational mentioning
confidence: 99%
“…Significant disparities currently exist among SSA countries in genomics research capacity (Adedokun et al 2016). South Africa has the highest genomics research output, which is reflected in the investments made in its genomics and biotechnology sector (Hardy et al 2008;Warnich et al 2011;Ndimba and Thomas 2008;Motari et al 2004). The study findings call for African governments to increase their investments in building local capacity, provide a sustainable research environment, and encourage joint genomics research among those affiliated with SSA universities.…”
Section: Overcoming Obstacles/challenges To Facilitate Translational mentioning
confidence: 99%
“…The most important class of the drug metabolizing enzymes is the cytochrome P450 (CYP450) family, which is involved in phase I metabolism of various endogenous and exogenous compounds, including the majority of clinically prescribed drugs (Warnich et al, 2011). CYP450 enzymes are heme oxygenases, found mainly in the liver.…”
Section: Drug Metabolism and Pharmacogenomicsmentioning
confidence: 99%
“…For example, a scoping analysis of 344 studies in health and allied sciences addressing patients', clinicians' and researchers' priorities for research, found that only nine considered the extent to which questions posed by researchers matched questions of relevance to patients and clinicians [12]. Furthermore, translation of pharmacogenomics into the clinic remains a challenge, especially in low and middle income countries that can benefit much from effective and safe therapeutic regimes [13].…”
Section: Looking Beyond the Laboratory Space: Responsible Innovationmentioning
confidence: 99%
“…These principles were outlined by Elinor Ostrom, Nobel Laureate in Economic Sciences in 2009 ( Table 1, with modifications by Pang) [14,15]. CPPM readers are encouraged to read the seminal works on the governance of the commons and institutional diversity by Ostrom [15,16], and the ways in which these can impact behavior in society, including our 21 st century knowledge society [8] that is being shaped by globalization of genomics and personalized medicine [5,11,13].…”
Section: Design Principles For Global Public Goodsmentioning
confidence: 99%